Serious Game Dynamic Stock Agroindustry Product as a Production Planning using Cournot Model - Saiful Bukhori; Windi Eka Y. R; Januar Adi P (International Journal of Supply Chain Management, 2019)
Stock management is an important part of Supply Chain Management (SCM). Stock dynamics in SCM agroindustry in this research was modelled by exploring SCM which was then simplified by using Cournot model. The results of this research can be used to monitor and create marketing strategies by agroindustry. Market structure will be an influential environment where agroindustry is located, if the environment is different, then the policies or strategies used in the market will also be different.